Preliminary estimation of nocturnal bird density in oil palm agroecosystem - Syed Hassan, Sharifah Nur Atikah; Puan, Chong Leong; Md Sharif, Badrul Azhar (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Previous studies had indicated that agricultural lands serve as habitats to various diurnal birds although emphasis on nocturnal species was often overlooked in such areas. A survey on nocturnal birds was conducted in oil palm smallholdings at Tanjung Karang, Kuala Selangor based on distance sampling method. The study aimed to estimate the density of nocturnal birds in the agroecosystem. During the two-month study period, a total of 40 sampling stations were visited between 2000 to 0000 hrs, with a 10-min silent listening at each station. The preliminary results from distance sampling indicated that oil palm smallholdings were habitats to several nocturnal birds including the Large-tailed Nightjar (Caprimulgus macrurus-3 individuals/ha), Spotted Wood Owl (Strix seluputo-5/10 ha), Sunda/ Collared Scops Owl (Otus lempiji- 5/100 ha), Oriental Bay Owl (Phodilus badius- 5/100 ha)and Barn Owl (Tyto alba-8/100 ha). Only a few Brown Wood Owls (Strix leptogrammica), Dusky Eagle Owls (Bubo coromandus) and Brown Boobooks (Ninox scutulata) were detected. The presence of a high density of nocturnal birds in oil palm smallholdings may be associated with the availability of food resources and suitable roosting areas.